In-situ TEM observation and MD simulation of the reaction and transformation of <100> loops in tungsten during H2+ & He+ dual-beam irradiation. (November 2021) - Ding, Yifan; Guo, Long; Li, Yipeng; Liu, Xinyi; Ran, Guang; Wu, Lu; Qiu, Xi; Deng, Huiqiu; Wu, Xiaoyong; Li, Yuanming; Huang, Xiuyin
Abstract: Low mobility <100> loops significantly affect the mechanical properties of body-centered cubic materials and their generation and evolution have been a hot research topic recently. However, there is still a lack of direct observation on the reaction of the formed <100> loops during subsequent irradiation, which hinders a better understanding of the degradation of mechanical properties induced by irradiation. Here, we reported for the first time that the reaction between <100> loops produced 1/2<111> loop through in-situ TEM observation during 30 keV H2 + & He + dual-beam irradiation in tungsten. Molecular dynamics simulation showed that this reaction required appropriate relative position of the initial <100> loops and high temperature that could induce <100> loop split into 1/2<111> segments and then transformed into 1/2<111> loop. Meanwhile, the evolution of <100> loops was in-situ observed. The average size and areal number density of <100> loops were quantified as a function of irradiation fluence.